Effect of Biofeedback on the Anxiety of Amateur Athletes: Biofeedback sobre la ansiedad de los deportistas. - Cantón, Enrique; Pérez-Córdoba, Eugenio; Estrada, Omar; Díaz-Rodríguez, Carlos; Peris-Delcampo, David (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
Biofeedback is an effective strategy to decrease levels of activation and anxiety. The purpose of this study is to determine the degree to which amateur athletes are able to learn to control their autonomic responses through biofeedback. The hypothesis of this study is that amateur athletes with biofeedback intervention will significantly decrease their level of psychophysiological activation compared to those without the intervention. Sixteen amateur marathon athletes participated, from the city of Andria de la Puglia, Italy. They were randomly assigned to two groups, one control and one experimental (i.e., biofeedback condition, which used peripheral temperature, skin conductance, and heart rate techniques). During the intervention period, there were six 15-minute individual sessions over two weeks. Anxiety was evaluated using the STAI survey, which is a subjective scale of activation and a psychophysiological profile. The statistical analysis used in this study is analysis of variance of repeated measurements was used with a significance level of .05. For the Post Hoc or a posteriori comparison, the Sidák and the Bonferroni procedure were conducted. A significant interaction was found between the evaluation conditions, timepoints, group, including peripheral temperature and in the skin conductance. The experimental group has significant lower activation compared to the control group, higher increase of the peripheral temperature and lower conductance. There is no difference in anxiety measured with the STAI. In conclusion, the biofeedback group has learned to control their autonomic responses, as indicated by a significant decrease in the level of psychophysiological activation, compared to the group without intervention.